The tolerance of oil palm (Elaeis guineensis) seedlings to Al stress is enhanced by citric acid and natural peat water - Agus Nur Hidayah; Sudirman Yahya; Didy Sopandie (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hidayah AN, Yahya S, Sopandie D. 2020. The tolerance of oil palm (Elaeis guineensis) seedlings to Al stress is enhanced by citric acid and natural peat water. Biodiversitas 21: 4850-4858. Management technology on soil containing high levels of Aluminum (Al) toxicity is still needed to be developed so that the growth and development of plants will be optimum. The aims of the research were to investigate the response of oil palm seedlings (Elaeis guineensis Jacq.) toward aluminum stress, and to evaluate the effects of several exogenous compounds to improve the tolerance of oil palm. The research was conducted from September 2018 to March 2019 at PT Gunung Sejahtera Ibu Pertiwi, Central Kalimantan. This research consisted of two nutrient culture experiments, namely: Al toxicity on oil palms seedlings and the role of various exogenous compounds to improve plant tolerances. The results revealed that the solution at concentrations of 400 ?M, 800 ?M, and 1600 ?M of Al significantly inhibited root growth, increased MDA levels, decreased the photosynthesis rate, activity of CAT and APX. Therefore, a solution at concentration of 400 ?M of Al can be used as the selection level of Al tolerant oil palm varieties on nutrient culture. Ethephon at concentrations of 25 ppm, 50 ppm, and 100 ppm inhibited root and shoot growth, increased MDA levels but reduced the photosynthesis rate, chlorophyll content, APX, and CAT activity. Addition of 25 ppm and 50 ppm of citric acid, 200 ppm and 300 ppm of peat water significantly increased root length, root dry weight, photosynthesis rate, chlorophyll content, carotenoids, CAT, and APX activities as MDA levels decreased. Addition of citric acid and peat water enabled seedlings of oil palm to improve their tolerance to Al stress on nutrient culture.